THE EFFECTIVENESS OF METACOGNITIVE READING STRATEGY TO TEACH DESCRIPTIVE READING TEXT - Fathul Bari (ICoTE Proceedings)
The purposes of this study were to find out the effectiveness of a metacognitive reading strategy to teach descriptive reading text and to find out how significant metacognitive reading strategy is for teaching descriptive reading text at tenth-grade students of SMA Islamiyah Pontianak in the Academic Year 2014/2015. In this study, the researcher used pre-experimental research design. The sample of this study was tenth-grade students of SMA Islamiyah Pontianak in the Academic Year 2014/2015. The researcher used deciding to sample as sampling technique. The researcher took one class (X IPS 2) which consisted of 24 students. The technique of collecting data was measurement technique. The tool of collecting data was written test in multiple-choice form. Based on the result of this study, the researcher concluded that using metacognitive reading strategy to teach descriptive reading text at tenth-grade students of SMA Islamiyah Pontianak in the Academic Year 2014/2015 was the to be applied for teaching and learning process descriptive reading text. Nevertheless, to achieve the teaching and learning goal by using metacognitive reading strategy to teach the descriptive reading text. The teacher should explain metacognitive reading strategy clearly, giving example, and practice. To make students understand the metacognitive reading strategy.